2015
DOI: 10.1016/j.seizure.2015.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Epileptic encephalopathy with electrical status epilepticus: An electroclinical study of 59 patients

Abstract: To evaluate the electroclinical features, treatment effectiveness, and outcome of 59 patients with epileptic encephalopathy with electrical status epilepticus during sleep. Methods: Medical-files of 59 patients with electrical status epilepticus during sleep were retrospectively evaluated for data concerning: history, physical and neurological examinations, sleep and awake EEG's, psychometric tests and brain MRI. Results: A total of 31 boys and 28 girls were identified. Patients were evaluated in two groups: s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 38 publications
(70 reference statements)
2
9
1
2
Order By: Relevance
“…Various degrees of intellectual deterioration were found in 18 of 22 patients (81%) in our cohort. Arhan et al [21] reported that 40.6% of their cohort showed cognitive decline in our country. Attention-deficit hyperactivity disorder was found in 9 of 44 patients in our cohort.…”
Section: Discussionmentioning
confidence: 75%
“…Various degrees of intellectual deterioration were found in 18 of 22 patients (81%) in our cohort. Arhan et al [21] reported that 40.6% of their cohort showed cognitive decline in our country. Attention-deficit hyperactivity disorder was found in 9 of 44 patients in our cohort.…”
Section: Discussionmentioning
confidence: 75%
“…ДЭПД являются облигатными ЭЭГ-паттернами при ряде форм эпилептических энцефалопатий, особенно сопровождающихся постоянной продолженной эпилептиформной активностью в фазу медленного сна. Это синдромы псевдо-Леннокса, Ландау-Клеффнера, энцефалопатия с электрическим эпилептическим статусом медленного сна [14,16,28]. Общими признаками ДЭПД на ЭЭГ при всех данных синдромах являются крайне высокий индекс эпилептиформной активности с нарастанием в фазу медленного сна и тенденция к диффузному распространению ДЭПД.…”
Section: Ch I Ld Neurology R U S S I a N J O U R N A L O Funclassified
“…Причины повреждающего воздействия продолженной эпилептиформной активности на функциональное состояние детского мозга точно не определены. В настоящее время предполагается несколько механизмов такого воздействия [16,25,28,46,89]:…”
Section: Ch I Ld Neurology R U S S I a N J O U R N A L O Funclassified
“…A significant decrease in seizure frequency (>50%) was observed in 35 (70%) of the 50 patients with seizures at the start of LEV therapy, and a positive EEG response was observed during the first 3-4 months of LEV therapy in 32 (45%) of the 71 patients. In addition, Arhan et al [62] performed a retrospective study to assess the efficacy of AED therapy in 59 children with ESES and demonstrated that LEV is one of the two most effective anti-ESES drugs.…”
Section: Electrical Se During Sleepmentioning
confidence: 99%